Kedudukan Advokat Mendampingi Tersangka dalam Proses Penyidikan - Novita, Rini (Universitas Medan Area, 2024)
This article or paper aims to Analyze the Regulation and Implementation of Legal Aid, as well as Assess the Role of Advocates in Ensuring Access to Justice. This descriptive research uses a normative juridical approach to analyze secondary data, such as regulations and legal literature, to evaluate regulations, identify legal loopholes, and assess policy implementation. Qualitative analysis is carried out to provide recommendations for policy improvement under the principle of justice. The results of the study show that the analysis of legal aid highlights the importance of assisting advocates in a fair justice system. Even though regulations are adequate, implementation still faces obstacles such as a lack of public awareness and limited advocates. Strengthening regulations, public education, and synergy between the government, advocates, and law enforcement are needed so that legal assistance is optimal in protecting human rights. Advocates play an important role in ensuring access to justice, protecting the rights of suspects, and ensuring that legal proceedings run according to the rules. With better collaboration, advocates can be guardians of justice and provide equitable legal protection without discrimination.